A Case of Recurrent Facial Pain Associated With a Pourfour du Petit Syndrome: A New Entity?. Issue 2 (23rd May 2013) - Collongues, Nicolas; Labouret, Pascale; Speeg, Claude; de, Jérôme
<x xml:space="preserve">Abstract</x> We report the case of a 38‐year‐old woman with a history of migraine who experienced an association of recurrent unilateral facial pain and Pourfour du Petit syndrome. The episodes occurred for between a few seconds and up to 3 minutes up to 6 times a day mimicking short‐lasting unilateral neuralgiform headaches with cranial autonomic symptoms. No lesional cause was found and the use of topiramate led to a nearly complete disappearance of the episodes. This new entity raises the question of a novel autonomic dysfunction in short‐lasting unilateral neuralgiform headaches with cranial autonomic symptoms or an unexpected presentation of migraine.